The couples psychotherapy progress notes planner - Berghuis, David J.; Jongsma, Arthur E., Jr., 1943-; O'Leary, K. Daniel, 1940- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2011)
'Now in a Second Edition, The Couples Psychotherapy Progress Notes Planner helps mental health practitioners reduce the amount of time spent on paperwork so more time can be spent with clients. The new edition covers an eclectic array of treatment approaches and corresponds with the behavioral problems and the DSM diagnostic categories found in The Couples Psychotherapy Treatment Planner. With new and updated information on the role of evidence-based practice in progress notes writing and the special status of progress notes under HIPAA, this guide provides marriage and family therapists with over 1,000 prewritten progress notes and treatment approaches for working with couples'--Provided by publisher.
Machine generated contents note: Alcohol Abuse* -- Anger* -- Anxiety* -- Blame* -- Blended Family Problems* -- Communication* -- Dependency -- Depression Due to Relationship Problems* -- Depression Independent of Relationship Problems* -- Disillusionment with Relationship* -- Eating Disorders* -- Financial Conflict* -- Infidelity* -- Internet Sexual Use -- Intimate Partner Violence - Intimate Terrorism* -- Intimate Partner Violence - Situational (Bi-directional) Couple Violence* -- Intolerance* -- Jealousy* -- Job Stress* -- Life-changing Events* -- Loss of Love/Affection* -- Midlife Transition Problems* -- Only One Partner Willing to Attend Therapy* -- Parenting Conflicts - Adolescents* -- Parenting Conflicts - Children* -- Personality Differences* -- Psychological Abuse* -- Recreational Activities Dispute* -- Religious/Spirituality Differences* -- Retirement* -- Separation and Divorce* -- Sexual Abuse* -- Sexual Dysfunction* -- Transition to Parenthood Strains* -- Work/Home Role Strain* -- * Indicates that selected Objective/Interventions are consistent with those found in evidence-based treatments.
Keywords: Couples Therapy -- Methods; Marital Therapy -- methods; Patient Care Planning